Immunological characterization of pleural effusions in pediatric patients - Flögel, Luca; Kaiser, Elisabeth; Hans, Muriel Charlotte; Goedicke-Fritz, Sybelle; Bous, Michelle; Abdul-Khaliq, Hashim; Poryo, Martin; Zemlin, Michael; Weber, Regine (Frontiers in Immunology, 2024)
BackgroundThe pleural cavity represents a unique immunological compartment that can mount inflammatory reactions during infections, after surgery and in chronic immunological diseases. The connection between systemic immune reactions in the blood and local immune reactions in pleural effusions remains unclear. This study provides the first comprehensive immunological characterization of paired blood and pleural effusion samples, utilizing combined cell and cytokine analyses in pediatric patients undergoing cardiac surgery.MethodsIn 30 pediatric patients (median age: 22 months) with pleural effusion after cardiac surgery for congenital heart defects, corresponding peripheral blood and pleural effusion samples were analyzed for their immune response. We used flow cytometry and multiplex immunoassays to quantify 14 T cell subpopulations and 12 T cell associated cytokines in each biosample.ResultsIL-6, IL-8, IL-10, TNF (p<0.0001) levels were significantly higher in pleural effusion compared to plasma. In contrast, IFN-γ, GM-CSF, IL-17A levels were lower in pleural effusion than in plasma (p ≤ 0.0005). In comparison to peripheral blood, there was a significantly higher proportion of T helper cells 1 (Th1, p=0.0023), T helper cells 17 (Th17, p=0.0334) and memory effector cytotoxic T cells (CD3+CD8+CD45RO+CD62L-, p=0.0449) in pleural effusion and the same trend was observed for memory effector Th cells (CD3+CD4+CD45RO+CD62L-, p=0.0633) and double-negative T cells (CD3+CD4-CD8-) (p=0.1085). Naïve Th cells (CD3+CD4+CD45RO-CD62L+) and naïve cytotoxic T cells (CD3+CD8+CD45RO-CD62L+) were slightly reduced in pleural effusion compared to peripheral blood (not significant).ConclusionImmunological factors in pleural effusions differed significantly from the corresponding blood samples in pediatric patients after cardiac surgery. The results suggest localized production of specific cytokines within the pleural space, while the distribution of other cytokines in pleural effusions appears to be more reflective of the systemic immune response. We found evidence that on the cellular level, the surface marker CD62L may play a key role in navigating T cells between the blood and pleural effusion. This study confirms that the pleural cavity harbors a unique lymphatic compartment, the analysis of which may be useful for both diagnostic and therapeutic purposes.